2016
DOI: 10.15761/tec.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative failures of the PFNa II spiral blade

Abstract: Background: The commonly encountered unstable geriatric trochanteric hip fractures are frequently managed with a proximal femoral nail and spiral blade. Although well recognized risks and complications including cut-out/backing-out of the blade have been reported; current literature has put less emphasis into describing the intra-operative problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…However, intraoperative complications are faced commonly but are not frequently reported. The literature review showed just a single report of two cases, in which the author had elucidated intraoperative complications, one being from an inability to lock the helical blade, and another case when there was a mismatch of the jig, due to which the blade could not be passed through the nail as reported by Siu et al [ 4 ]. Also, joint disruption by the blade further would aggravate the process of arthritis in this age group and can be a probable cause of painful weight bearing even after 4 months of the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, intraoperative complications are faced commonly but are not frequently reported. The literature review showed just a single report of two cases, in which the author had elucidated intraoperative complications, one being from an inability to lock the helical blade, and another case when there was a mismatch of the jig, due to which the blade could not be passed through the nail as reported by Siu et al [ 4 ]. Also, joint disruption by the blade further would aggravate the process of arthritis in this age group and can be a probable cause of painful weight bearing even after 4 months of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a developing world, where multiple indigenous manufacturers are making implants, some standardized and some not, operating surgeons are exposed to newer intra-operative struggles with the implant leading to prolonged surgical duration, increased blood loss, larger incisions as well as poorer outcomes. Only a single article enlists intra-operative inability to lock the blade and another case where mismatch of jig and the blade was reported, causing the intra-operative struggle shown by Siu et al [ 4 ]. We report a case, where the helical blade of the implant broke while trying to remove the blade from the bone due to a size mismatch.…”
Section: Introductionmentioning
confidence: 99%